Numerical method for front tracking in mold filling modeling in composite injection molding: non-reacting system - Mohammad Fahrurrozi; John R. Collier (Jurnal Rekayasa Proses, 2009)
Mold filing simulation is important in mold design for liquid composite molding. Cost of commercial software for mold filling simulation is very expensive for average Indonesian companies. Therefore a more affordable simulation program is necessary to promote development of domestic technology related to liquid composite molding. This paper presents 3-dimension mold filling model based on control volume finite difference (CV-FD) numerical method on fixed grids. Front tracking was performed using volume of fluid method (VOF) implemented on CV-FD. Velocity field was computed using Darcy's equation. Computation was implemented on Fortran while contour plot were prepared using Matlab. The developed model predicts well gate pressure obtained experimentally. Since experimental data for front advancement is not available, calculation results were compared with results for other software developed by US’s NIST. The developed model predict front position obtain by the other software quite well.